Evidence of epithelial-mesenchymal transition in canine prostate cancer metastasis - Fonseca-Alves, Carlos Eduardo [UNESP]; Kobayashi, Priscila Emiko [UNESP]; Rivera-Calderon, Luis Gabriel [UNESP]; Laufer-Amorim, Renee [UNESP] (Elsevier B.V., 2015)
The epithelial mesenchymal transition (EMT) is a fundamental event responsible for the invasiveness and metastasis of epithelial tumours. The EMT has been described in many human cancers, but there are few reports of this phenomenon in veterinary oncology. Due to the importance of this process, the current study evaluated mesenchymal and epithelial marker protein expression in prostate lesions from dogs. Our results indicate both a loss of E-cadherin and translocation of P-catenin from the membrane to the cytoplasm and nucleus in the tumour group. Vimentin expression in the tumour group was higher than in normal tissue. All of the metastases were positive for prostate-specific antigen, pan-cytokeratin and E-cadherin, although fewer positive cells were present than in the primary tumours. The immunohistochemical results showed a loss of epithelial markers and a gain of a mesenchymal marker among metastatic cells, suggesting that the EMT occurs during the metastatic process of canine prostate carcinoma. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dog; Prostate cancer; Immunohistochemistry; Epithelial-mesenchymal crosstalk